Development of Skinner-Based 'Civic Domain' E-Learning Platform to Enhance Civic Education Motivation at Undiksha Lab High School - Pratyastoma, Gede Aditya; Sukadi; I Wayan Budiarta; I Wayan Gede Griyawana; Komang Deta Satriawan; Rasyid Ridho (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2026)
The low motivation of students to learn in Civic Education shows the need for learning media innovations that are more interactive and in accordance with the characteristics of 21st century students. One relevant approach is the development of digital media based on Skinner's reinforcement theory, which emphasizes the gradual provision of stimulus, response, and positive reinforcement. This research aims to develop the Civic Domain e-learning platform as a valid, practical, and potentially effective Civic Education learning media to increase students' learning motivation. The method used is Research and Development (R&D) with the ADDIE model, but the research is focused on the needs analysis stage as well as the design and development of the initial product. Needs data were obtained through questionnaires, interviews, and observations involving teachers and students of Undiksha Lab High School. The results of the analysis show that PKn learning still tends to be monotonous, does not utilize interactive media, and has not been able to generate motivation to learn. Based on these findings, a prototype of the Civic Domain platform was designed and developed with automated quiz features, digital discussion forums, badge systems, and instant feedback. These initial products are then validated by material experts, media experts, and learning experts to ensure the feasibility of content, display, and pedagogical aspects. The conclusion of the study shows that the Civic Domain platform is worthy of further development as a learning medium for PKn.